2021
DOI: 10.1038/s41467-021-23475-4
|View full text |Cite
|
Sign up to set email alerts
|

Caerulomycin and collismycin antibiotics share a trans-acting flavoprotein-dependent assembly line for 2,2’-bipyridine formation

Abstract: Linear nonribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs) template the modular biosynthesis of numerous nonribosomal peptides, polyketides and their hybrids through assembly line chemistry. This chemistry can be complex and highly varied, and thus challenges our understanding in NRPS and PKS-programmed, diverse biosynthetic processes using amino acid and carboxylate building blocks. Here, we report that caerulomycin and collismycin peptide-polyketide hybrid antibiotics share an assembly l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…22 Changes in ACP S-acylation can be examined based on an ejected Ppant-characteristic ion during MS/MS analysis. 23,24 As a result, two intermediates were revealed to be dominantly tethered on MmcB-I (Figures 3 and S4 and S5). Compared with AHBA−GlcNAc (2), one of the intermediates is a -42 Da product (3) that is consistent with the assignment to AHBA−GlcN by the loss of an acetyl group.…”
Section: Resultsmentioning
confidence: 95%
“…22 Changes in ACP S-acylation can be examined based on an ejected Ppant-characteristic ion during MS/MS analysis. 23,24 As a result, two intermediates were revealed to be dominantly tethered on MmcB-I (Figures 3 and S4 and S5). Compared with AHBA−GlcNAc (2), one of the intermediates is a -42 Da product (3) that is consistent with the assignment to AHBA−GlcN by the loss of an acetyl group.…”
Section: Resultsmentioning
confidence: 95%
“…Caerulomycins (CAEs) and collismycins (COLs), the two groups of structurally related 2,2′-bipyridine antibiotics that differ from each other primarily by lacking or having sulfur decoration (Figure ), display a wide variety of biological properties such as anti-infection, cytotoxicity, immunosuppression, and neuron protection. In line with their structural similarity, CAEs and COLs share the assembly line biogenesis of a modular polyketide synthase (PKS)/NRPS hybrid system, which templates the sequential incorporation of the same monomers picolinic acid, malonyl CoA, l -cysteine, and l -leucine. , Recently, we reported that this assembly line guides the formation of similar desulfurized (for CAEs) and sulfurized (for COLs) 2,2′-bipyridine intermediates with the association of a flavoprotein partner functioning in trans (Figure ). Subsequent l -leucine extension, which does not contribute any atoms to either CAEs or COLs, determines the fate of the different 2,2′-bipyridine intermediates, leading to the final products with or without sulfur decoration . Common post-PKS/NRPS modifications include the hydrolysis of the C-terminally extended leucinyl residue and the generation of a rarely found oxime functionality that is characteristic of both CAEs and COLs. ,, During this process, the reductive conversion of the nascent carboxylic group into an aldehyde, which is necessary for the subsequent transamination and oxidation steps, remains to be elucidated (Figure ).…”
mentioning
confidence: 99%
“…In contrast, omitting the LMW thiol CoA from the reaction mixtures had little effect, questioning the necessity of CoA-thiolation for CaeB2-catalyzed reduction (Figure S6). To clarify this point, we determined whether 2,2′-bipyridine-CoA ( 4 ) is an intermediate during carboxylate reduction. CaeB2 was incapable of using synthetic 4 ([M + H] + m / z : calcd.…”
mentioning
confidence: 99%
See 2 more Smart Citations